2016
DOI: 10.1093/nar/gkw742
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin recruitment of activated AMPK drives fasting response genes co-controlled by GR and PPARα

Abstract: Adaptation to fasting involves both Glucocorticoid Receptor (GRα) and Peroxisome Proliferator-Activated Receptor α (PPARα) activation. Given both receptors can physically interact we investigated the possibility of a genome-wide cross-talk between activated GR and PPARα, using ChIP- and RNA-seq in primary hepatocytes. Our data reveal extensive chromatin co-localization of both factors with cooperative induction of genes controlling lipid/glucose metabolism. Key GR/PPAR co-controlled genes switched from transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 73 publications
5
57
0
3
Order By: Relevance
“…In the fed state, PPARα activity is enhanced through insulin-activated MAPK and glucose-activated PKC, while glucagon-activated PKA and AMPK increase PPARα signaling in fasting (49). Moreover, the fasting response is co-controlled by PPARα and GRα, which show extensive chromatin colocalization and interact to induce lipid metabolism genes upon prolonged fasting through genomic AMPK recruitment (110). Conversely, GRβ antagonizes glucocorticoid signaling during fasting via inhibition of GRα and PPARα, thus increasing inflammation and hepatic lipid accumulation (111).…”
Section: R E V I E W S E R I E S : N U C L E a R R E C E P T O R Smentioning
confidence: 99%
“…In the fed state, PPARα activity is enhanced through insulin-activated MAPK and glucose-activated PKC, while glucagon-activated PKA and AMPK increase PPARα signaling in fasting (49). Moreover, the fasting response is co-controlled by PPARα and GRα, which show extensive chromatin colocalization and interact to induce lipid metabolism genes upon prolonged fasting through genomic AMPK recruitment (110). Conversely, GRβ antagonizes glucocorticoid signaling during fasting via inhibition of GRα and PPARα, thus increasing inflammation and hepatic lipid accumulation (111).…”
Section: R E V I E W S E R I E S : N U C L E a R R E C E P T O R Smentioning
confidence: 99%
“…In addition, dexamethasone was shown to increase AMPK activity in hepatocytes while decreasing it in adipocytes (Christ-Crain et al, 2008). Finally, a physical link between phospho-AMPK and phospho-GR was shown in complex with PPARa to increase the transcriptional activity of the latter upon starvation (Ratman et al, 2016). These studies show that AMPK-GR interaction impacts on GR transcriptional activity.…”
Section: Discussionmentioning
confidence: 71%
“…Only scant studies have reported a link between AMPK signaling and GR signaling, and all in metabolic organs and cells (Liu et al, 2016;Nader et al, 2010;Ratman et al, 2016). Indirect AMPK activation is observed in muscle cells where dexamethasone treatment induces mitochondrial dysfunction leading to decreased ATP, thus activating AMPK (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, GR binds the PDK4 enhancer in concert with PPARα, but GR represses PDK4 induction [201]. So, in GC resistant conditions, more PDK4 induction is expected to lead to more pyruvate accumulation and L-lactate formation (Figure 2).…”
Section: Major Consequences Of Gcr In Sepsismentioning
confidence: 99%